Empowering Smart Aging: Insights into the Technical Architecture of the e-VITA Virtual Coaching System for Older Adults - Naccarelli, Riccardo; D’Agresti, Francesca; Roelen, Sonja Dana; Jokinen, Kristiina; Casaccia, Sara; Revel, Gian Marco; Maggio, Martino; Azimi, Zohre; Alam, Mirza Mohtashim; Saleem, Qasid; Mohammed, Abrar Hyder; Napolitano, Giulio; et al. (Sensors (Basel, Switzerland), 2024)
With a substantial rise in life expectancy throughout the last century, society faces the imperative of seeking inventive approaches to foster active aging and provide adequate aging care. The e-VITA initiative, jointly funded by the European Union and Japan, centers on an advanced virtual coaching methodology designed to target essential aspects of promoting active and healthy aging. This paper describes the technical framework underlying the e-VITA virtual coaching system platform and presents preliminary feedback on its use. At its core is the e-VITA Manager, a pivotal component responsible for harmonizing the seamless integration of various specialized devices and modules. These modules include the Dialogue Manager, Data Fusion, and Emotional Detection, each making distinct contributions to enhance the platform’s functionalities. The platform’s design incorporates a multitude of devices and software components from Europe and Japan, each built upon diverse technologies and standards. This versatile platform facilitates communication and seamless integration among smart devices such as sensors and robots while efficiently managing data to provide comprehensive coaching functionalities.